Knowledge and practices of health care professionals to prevent surgical site infection in a tertiary health care centre - Patil, Vaibhav B.; Raval, Ravi M.; Chavan, Ganesh (International Surgery Journal, 2018)
Background: In spite of advanced operative techniques, availability of higher antibiotics, modern sterilization techniques, higher rate of SSI in government set up after major surgeries is quiet worrisome. Present study is an attempt to assess knowledge and practices of health care professionals to decrease incidence of SSI and to determine their relationship with each other. Methods: This is cross sectional study conducted in one of the tertiary institute in western Maharashtra. Data collection was done by using pre-tested, structured questionnaire. We assessed knowledge and practices followed in wards and operation theatre and compared with standard practices according to WHO infection control protocols. We analyzed data according to Low (<60%), moderate or good (60-80%) and >80% means high knowledge and practices using 3-point Likert scale (never practiced, sometimes practiced, and always practiced). Subgroup analysis will be made by dividing participants in 3 groups mainly consultants (faculty), residents and interns, and staff nurses. Results: Authors found poor knowledge among all three subgroups and in assessment of level of practices, we found that 68.75 % of consultants were following very high level of practices followed by staff nurses (64.51%) and then Interns and residents (49.15%) and while assessing relationship between knowledge and practices in each subgroup by calculating spearman’s Rho coefficient (R), authors found that for interns and residents, P value is 0.025, so association is statistically significant. Conclusions: It can be concluded that health care professionals in the current study have good practices level regarding infection control but knowledge of surgical site infection prevention activities among those was found low. It emphasizes importance of providing training programs for newly joined students, staff nurses and for consultants about infection control protocols at regular intervals.